Lateral target strength of Antarctic krill - Hewitt, Roger P.; Demer, David A. (ICES Journal of Marine Science, 1996)
An area of high krill ( Euphausia superba Dana) density was continuously monitored with down-looking and side-looking sonars over a period of 24 h. Measurements of volume backscattering strength were used to describe the density of krill with depth and the vertical movement of krill over time. In situ measurements were made of dorsal aspect target strength (TS) and, as krill moved into the near-surface layer (0–15 m), in situ measurements were made of lateral-aspect TS. The probability density function (PDF) of TS measurements made with the down-looking transducer had a mode at approximately −73 dB. The PDF of TS measurements made with the side-looking transducer was broader with a mode at approximately −67 dB. Sampled krill had a bi-modal length distribution with a major mode at 44 mm and a minor mode at approximately 30 mm.